PALATAL PATTERNS BASED RGB TECHNIQUE FOR PERSONAL IDENTIFICATION - Anjali A Bhadre , Harshvardhan P Ghongade , Dr. Ravindra N Katiyar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Biometric system is an alternative way to the traditional identity verification methods. This research article provides an overview of recently / currently used single and multiple biometrics based personal identification systems which are based on human physiological (such as fingerprint, hand geometry, head recognition, iris, retina, face recognition, DNA recognition, palm prints, heartbeat, finger veins, footprints and palates) and behavioral (such as body language, facial expression, signature verification and speech recognition) characteristics